Nuremberg diary - Gilbert, G. M., 1911-1977. (New York : Da Capo Press, 1995)
The diary by G. M. Gilbert, Ph. D., formerly prison psychologist at the Nuremberg Trial of the Nazi War criminals.
Originally published: New York : Farrar, Straus, 1947. With the addition of 24 photos from the 1961 ed.
Includes index.
Keywords: Gilbert, G. M., -- 1911-1977 -- Diaries; Nuremberg War Crime Trials, Nuremberg, Germany, 1946-1949.; War criminals -- Germany -- Psychology; Prison psychologists -- United States -- Diaries